Pedagogical Conditions of Formation of Professional Communication Culture of the Future Transport Industry Teachers-Engineers - Kochyna, Valentyna (Pedagogical Discourse, 2016)
The necessity of professional communication formation of culture for future transport industry teachers-engineers is substantiated in the article. The essence of the concept «the culture of professional communication for transport industry teacher-engineer» was developed with analysis of scientific literature. It is determinate, that the basis of culture professional communication consists of a communicative competence. Culture formation of professional communication provides the creation of definition pedagogical conditions in higher educational establishment during the educational process. The content of pedagogical conditions that allowed to form the culture of professional communication for future teacher-engineers are considered at the article. These pedagogical condition are: the development and realization of elective courses of content of culture professional communication formation for future transport industry teachers-engineers by kinds of their engineering professional activity; the development and realization of multimeter method of formation of culture professional communication for transport industry future teachers-engineers; the development and realization of complex form that provides a formation of culture professional communication for future transport industry teachers-engineers and connects preparative (teacher-centred teaching and private tuition) and main (cooperative learning) forms of interactive training. The content of each pedagogical condition is fond. The first pedagogical condition provides for development of elective courses of content of education that refers for the formation of culture professional communication. Special aspects and selection principle of content of education in accordant to kinds of their engineering activity for future transport industry teachers-engineers (design, operating, repair, organizationally-administrative) are specified. It should take into account for formation of culture professional communication of future specialists. The second pedagogical condition is connected with development of multimeter method that combine explanatory-illustrative, procreational, problem exposition, partly-searching and research methods for the formation of culture professional communication of future teachers-engineers. The third pedagogical condition is determinated with the participation of the future specialists for active professional-pedagogical communication with using interactive forms of training. They are preparative (teacher-centred teaching and private tuition) and main (cooperative learning). Key words: pedagogical conditions, culture, professional communication, transport industry teacher-engineers, elective courses of content, multimeter method, complex form.